School zoning and equal education access in Indonesia - Yunike Sulistyosari; Amika Wardana; Siti Irene Astuti Dwiningrum (Institute of Advanced Engineering and Science, 2023)
The implementation of the school zoning policy in the student admission system of the lower secondary schools since 2017 aims to promote equal educational access for all pupils in Indonesia. The new policy has been constantly under scrutiny, confusing the grounds, particularly for parents whose kids failed to get admitted. Based on a qualitative study in the typical Indonesian regency of Temanggung, Central Java, the article underscores that the geographical based of school zoning system might have never assured equal education access for all pupils as the available seats in all state-owned public schools combined do not meet the number of prospectus students in the regency per annum. Moreover, there are some different understandings among government officials, particularly regent educational officers, schools’ principals, and teachers, regarding the primary goals of the policy as well as attention to its long-term unintended impacts. Under this zoned student admission system, some traditionally reputable and favorite state-owned public schools have to admit students with diverse academic motivation and performance, including the lower one, which eventually leads them to struggle to maintain academic quality and reputation.